Prosopagnosia and the role of face-sensitive areas in race perception - Pauline Schaller; Anne-Raphaëlle Richoz; Justin Duncan; Peter de Lissa; Roberto Caldara (Scientific Reports)
Abstract Race is rapidly and effortlessly extracted from faces. Previous fMRI studies have reported race-related modulations in the bilateral Fusiform Face Areas (FFAs) and Occipital Face Areas (OFAs) during the categorization of faces by race. However, our recent findings revealed a comparable Other-Race Categorization Advantage between a well-studied case of pure acquired prosopagnosia—patient PS—and healthy controls. Notably, PS demonstrated faster categorization by race of other—compared to same-race faces, similar to healthy participants, despite sustaining lesions in the right OFA (rOFA) and left FFA (lFFA). This observation suggests that race processing can occur effectively even with damage to core face-sensitive regions, challenging the functional significance of race-related activations in the rOFA and lFFA observed in healthy individuals with fMRI. To address this apparent contradiction, we tested PS and age-matched controls during the categorization by race of same- to other-race morphed faces. Our data showed that PS required more visual information to accurately categorize racially ambiguous faces, indicating that intact rOFA and/or lFFA are crucial for extracting fine-grained racial information. These results refine our understanding of the functional roles of these key cortical regions and offer novel insights into the neural mechanisms underlying the perception of face race and prosopagnosia.